An Architecture-Based Adaptation Framework for Soft Real-Time Applications - Xiaoan Bao; Na Zhang; Ning Gui; Jinyu Song (Dianxin kexue)
Driven by the proliferation of mobile and pervasive computing, real-time systems are increasingly used in dynamic changing environments with variable user needs, hosting real-time applications ranging in number and nature over time. However, existing adaptation frameworks normally are incapable to cope with other competing and changing concerns. This paper proposes an architecture-based framework for managing real-time components' dependence and lifecycle in an effective and uniform way. A real-time component runtime service is proposed here to maintain the global view, control the whole lifecycle of the components and keep existing real-time componentsˊ promised contracts in the face of run-time changes. This framework is designed to be easily extended with other constraint resolving policies as well as dependence descriptions languages and can be used to provide real-time computing services for cloud computing. At end of this paper, the framework is tested from both adaptation and performance aspects by a simulated control application.